Aplikasi Indigenous Microorganism (Em-4) dan Pupuk Kompos Terhadap Pertumbuhan dan Produksi Tanaman Cabai Merah (Capsicum annum L.) pada Tanah Ultisol - Ratna Shanti (Mulawarman University, 2019)
Red Chilli is commodity of vegetable that has high economic value, but still has slow productivity. The objective of this study was identify the effect of indigenous microorganism (EM 4) application and compost to increased the growth and yield of Red Chilli Plant (Cappcicum annum L) on Ultisol. Field trial was conducted on Ultisols in Horticulture Experimental Station, BatuahLoajanan, Kutai Kartanegara. The soil was characterized by low fertility status. The amount of organic matter and microbial acivity are very low. This trial was started on January until April 2017 using Split Plot Design with three replications Main plot consisted of two levels treatment i.e. without EM-4 (E0) as control and Effective Mikroorganisms-4 (E). Sub-plot was four rates of organic compost i.e. 0, 10, 20 and 30 tons ha-1 and chili was used as test plant.Results indicated that EM-4 treatment showed a significant effect on fruit yield of chilli. It increased the fruit yield 38 percent compare to control. Compost application significantly increased on fruit yield. The relationship between unfermented compost rate and fruit yield shows a linear regression YE0 = 1.699 + 0.047 X (r = 0.95) and quadratic regression for EM-4 fermented compost YE1 = 1,175 + 0,319 X – 0.007 X2(R2 = 0.603). Optimum compost rate was 23 ton.ha-1.To increased fruit yield of chilli, EM-4 fermented compost should be applied into and it can decreased compost rate application.